SENSIBILIDADE DA Macrophomina phaseolina A DIFERENTES FUNGICIDAS - da Silva Soares , Rayssa; de Souza da Silva, Talísia; da Silva Fernandes , Brenda; André Sganzerla Graichen , Felipe (ANAIS DO ENIC, 2026)
-